2017
DOI: 10.17261/pressacademia.2017.683
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a talent management measurement instrument

Abstract: Purpose-One of the most important internal resources of the organizations are talented employees. It is very important to invest in talented employees which is a value-created resource for the organizations because in the long run it provides sustainable competitive advantage and high performance. This study aims to fill the gap through conceptualizing and developing a talent management measurement instrument. Methodology-We established a scale incorporating six dimensions of talent management. Data were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…Yener, Gurbuz, and Pinar (Yener et al, 2017) also concluded that vocational training is one of the top-rated talent management practices. This practice is very well perceived when employees' individual aspirations coincide with the organisation's needs (Kadam et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Yener, Gurbuz, and Pinar (Yener et al, 2017) also concluded that vocational training is one of the top-rated talent management practices. This practice is very well perceived when employees' individual aspirations coincide with the organisation's needs (Kadam et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…The main goal is not only to make the human resources function operates more efficiently, but to create an integrated system for managing people which lets the organization rapidly and effectively respond to business needs (Besrsin, 2010). Talent Management Dimensions According to (Yener et al, 2017) the talent management dimensions can be categorized into five areas:…”
Section: Talent Management Strategies In Hotelsmentioning
confidence: 99%
“…The research model suggests that talent management has a direct impact on employee performance, talent management as independent variable consists of planning, developing & attracting, workplace culture, recruitment & retention and rewarding & compensation (Yener et al, 2017), employee performance as dependent variable is measured through terms of financial prospective, internal process prospective & guest prospective (Humaid, 2018).…”
Section: Research Modelmentioning
confidence: 99%
See 2 more Smart Citations